Design and Development of Low Temperature Community Solar Dryer for Oily and Hard Edible Produces - Kumari, Shruti; Kumari, Renu; Choudhary, Shilpa; Kumar, Sanjay (Journal of the Institute of Engineering, 2020)
Horticulture produce have very high-water content, sometimes more than 90% by volume. Several of them are oily and hard. These horticulture produce have very high count of free radicals and are medicinal in nature. Usually, these are grown in scattered places in rural areas on sidelines of regular agriculture, far from the market place. Their price slumps during seasons and increase exponentially after it, due to short lifetime and absence of good transportation network, cost-effective proper preservation technology as well as specialized transportation vehicles. In this paper, Small state of the art family size solar dryer of 5 kg per day is designed to dry these produces in a single day and validated in real time experiments. The dryer is capable of maintaining desired temperature range to extended period even after sunshine, with the help of High Heat Capacity Material and Phase Change Material. Humidity removal mechanism is also introduced to reduce drying time by at least two hours.